Biphenyl Modulates the Expression and Function of Respiratory Oxidases in the Polychlorinated-Biphenyls Degrader Pseudomonas pseudoalcaligenes KF707 - Sandri, Federica; Fedi, Stefano; Cappelletti, Martina; Calabrese, Francesco M.; Turner, Raymond J.; Zannoni, Davide (Frontiers in Microbiology, 2017)
Pseudomonas pseudoalcaligenes KF707 is a soil bacterium which is known for its capacity to aerobically degrade harmful organic compounds such as polychlorinated biphenyls (PCBs) using biphenyl as co-metabolite. Here we provide the first genetic and functional analysis of the KF707 respiratory terminal oxidases in cells grown with two different carbon sources: glucose and biphenyl. We identified five terminal oxidases in KF707: two c(c)aa3 type oxidases (Caa3 and Ccaa3), two cbb3 type oxidases (Cbb31 and Cbb32) and one bd type cyanide-insensitive quinol oxidase (CIO). While the activity and expression of both Cbb31 and Cbb32 oxidases was prevalent in glucose grown cells as compared to the other oxidases, the activity and expression of the Caa3 oxidase increased considerably only when biphenyl was used as carbon source in contrast to the Cbb32 oxidase which was repressed. Further, the respiratory activity and expression of CIO was up-regulated in a Cbb31 deletion strain as compared to W.T. whereas the CIO up-regulation was not present in Cbb32 and C(c)aa3 deletion mutants. These results, together, reveal that both function and expression of cbb3 and caa3 type oxidases in KF707 are modulated by biphenyl which is the co-metabolite needed for the activation of the PCBs-degradation pathway.